Implementasi Perangkat Lunak Attention Distraction Test - Aan Darmawan Hangkawidjaja; Ratnadewi Ratnadewi; Priska Analya; Ira Adelina (Universitas Kristen Maranatha, 2023)
Attention distraction test (ADT) is a tool that measures attention. ADT has lights in form of a box which can be adjusted how many lights can be turned on. The distraction of this test comes in form of the presence of other lights around the targeted lights. The aim of this study is to test the software implementation of attention and distraction test. Importance of the study are ADT limitations in variation of the distraction and recording the answer. ADT goes through two stages, first is testing all devices function. Second, design will be tested on respondents to analyze the results. If improvements are still needed, design and improvements will be made. Results show software can be used properly to measure a person's attention level. If respondent answer correctly and the reaction time is faster, it means that respondent has a better level of attention. Suggestions is to add respondent personal background, alternative colors of distraction lights and complete the data recap with sum of the correct answers and average time reaction.